2023
DOI: 10.3389/fimmu.2023.1230264
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and novel therapeutics of regulatory T cell subsets and interleukin-2 therapy in systemic lupus erythematosus

Yi-Giien Tsai,
Pei-Fen Liao,
Kai-Hung Hsiao
et al.

Abstract: Systemic lupus erythematosus (SLE) is a heterogeneous multisystem inflammatory disease with wide variability in clinical manifestations. Natural arising CD4+ regulatory T cells (Tregs) play a critical role in maintaining peripheral tolerance by suppressing inflammation and preventing autoimmune responses in SLE. Additionally, CD8+ regulatory T cells, type 1 regulatory T cells (Tr1), and B regulatory cells also have a less well-defined role in the pathogenesis of SLE. Elucidation of the roles of various Treg su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 127 publications
0
4
0
Order By: Relevance
“…Further studies revealed that in lupus nephritis patients, IL-17 was correlated with the SLE disease activity index (SLEDAI) [48][49] . A higher rate of Treg apoptosis was correlated with SLE severity, suggesting that CD4+ Treg cell abnormalities also affect immune tolerance in SLE patients [50] . It has been established that IL-2 levels and the IL-2/STAT5 signaling pathway control the quantity and functionality of CD4+ Tregs [51] .…”
Section: T Cells and T Cell Co-stimulator Blockersmentioning
confidence: 99%
“…Further studies revealed that in lupus nephritis patients, IL-17 was correlated with the SLE disease activity index (SLEDAI) [48][49] . A higher rate of Treg apoptosis was correlated with SLE severity, suggesting that CD4+ Treg cell abnormalities also affect immune tolerance in SLE patients [50] . It has been established that IL-2 levels and the IL-2/STAT5 signaling pathway control the quantity and functionality of CD4+ Tregs [51] .…”
Section: T Cells and T Cell Co-stimulator Blockersmentioning
confidence: 99%
“…Immune tolerance was also influenced by CD4+ Treg cell abnormalities in SLE patients, where an increased rate of Treg apoptosis was correlated with disease severity [55]. The IL-2/STAT5 signaling pathway and IL-2 level was shown to regulate the number and function of CD4+ Treg cells [56]. In mice and SLE patients, treatment with low-dose recombinant IL-2 was found to promote Treg cell-mediated beneficial activities in disease manifestations and to raise the circulating Tfr/Tfh ratio, which was associated with increased renal damage and reduced anti-dsDNA titers.…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
“…By inhibiting the activity of Teffs, Tregs help to maintain immune tolerance and prevent excessive or inappropriate immune responses. 13 Tregs that have higher amounts of IL-2R alpha (also called CD25) can bind IL-2 better. This takes IL-2 away from activated Teffs, which are immune cells that fight infection.…”
Section: Immunosuppression and Its Impacts On Pathology And Cancermentioning
confidence: 99%
“…IL-35 acts to suppress the immune response of Teffs, which play a role in the adaptive immune response. By inhibiting the activity of Teffs, Tregs help to maintain immune tolerance and prevent excessive or inappropriate immune responses . Tregs that have higher amounts of IL-2R alpha (also called CD25) can bind IL-2 better.…”
Section: Mechanisms Of Treg-mediated Immunosuppression and Its Impact...mentioning
confidence: 99%